Movements and Territorial Conflicts in Latin America - Fernandes, Bernardo Mançano [UNESP]; Welch, Cliff (Oxford University Press (OUP), 2023)
Latin America has undergone an intense struggle for land. Indigenous peoples, peasants, and the descendants of fugitive slaves have resisted the expropriation of their territories for five centuries. This chapter examines land struggles in the region, analyzing territorial domination and resistance. It argues that land occupations have served to promote the cultural survival of peoples being forcefully expropriated. Their expulsion is more than a political or economic problem, it is a societal problem, as it “others” and excludes certain ways of life from the Western Civilization project. The chapter describes how social movements organize to fight for land, how families prepare to change their destinies and how governments and corporations respond to land occupations. The fight for a fraction of territory is a struggle for the basic conditions of life and citizenship. A people cannot live without territory; therefore, groups in every Latin American country permanently question territorial control. A typology helps differentiate between private and public land occupations and processes of land reclamation. The chapter also analyzes diverse strategies of spatial production used by peasants to establish their territories and by original peoples to recover theirs. The study examines the unique characteristics of land occupations by peasants and indigenous peoples, as well as their different social formations and world views. In conclusion, the chapter argues that territorial disputes are also disputes over divergent models of development. Land occupations are fundamental to the agrarian question and will continue to occur so long as land ownership remains concentrated.
Keywords: Agribusiness; Indigenous peoples; Occupation; Peasantry; Socio-territorial movements; Territory